2021
DOI: 10.3390/nu13093100
|View full text |Cite
|
Sign up to set email alerts
|

Social Capital and Self-Perceived Quality of Life-Interrelated Predictors of Mediterranean Diet Adherence in Older Adults

Abstract: Living a healthy life in a supporting environment are key elements towards higher diet quality in older age. The Mediterranean Diet in Older Adults (MINOA) study collected cross-sectional data from adults ≥65 years old (n = 436) from April 2014 to November 2015 in rural Crete, aiming to understand the interrelations between Mediterranean Diet adherence, Social Capital and Health-Related Quality of Life (HRQL). Multivariate linear regression, carried out using SPSS 20.0, revealed that both Social Capital and HR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 57 publications
3
0
0
Order By: Relevance
“…Our findings showed a significant positive correlation between social capital and quality of life among older Chinese people, which was similar to previous findings (Apostolaki et al, 2021; Sun & Lu, 2020; Yang et al, 2020). This was further confirmed by our regression analysis that found that social capital positively predicts quality of life and is an important protective factor for quality of life, which was consistent with the findings of Lane et al (2020).…”
Section: Discussionsupporting
confidence: 93%
“…Our findings showed a significant positive correlation between social capital and quality of life among older Chinese people, which was similar to previous findings (Apostolaki et al, 2021; Sun & Lu, 2020; Yang et al, 2020). This was further confirmed by our regression analysis that found that social capital positively predicts quality of life and is an important protective factor for quality of life, which was consistent with the findings of Lane et al (2020).…”
Section: Discussionsupporting
confidence: 93%
“…Social capital positively predicts diet quality of the study population, both directly and indirectly. This finding corroborates the conclusion from previous studies that social capital is a protective factor of dietary guidelines adherence (37,38). Additionally, a recent study conducted in Australia indicates that social isolation is correlated to poor diet quality in older adults (39).…”
Section: Discussionsupporting
confidence: 91%
“…In accordance with our findings, a plethora of studies around the world in older adults, both men and women, have also highlighted the positive association between MD and HRQOL, despite using different questionnaires [49][50][51][52][53][54]. The SUN cohort with 11,015 participants and a 4-year follow-up found an independent association between MD compliance and all the physical and many of the mental health domains of the SF-36 questionnaire [55].…”
Section: Discussionsupporting
confidence: 90%